Effect of addition of different carbon materials on hydrogel derived carbon material for high performance electrochemical capacitors. (20th December 2015) - Barzegar, Farshad; Bello, Abdulhakeem; Guellati, Ouanassa; Momodu, Damilola Y.; Harat, Aicha; Dangbegnon, Julien K.; Guerioune, Mohamed; Manyala, Ncholu
Graphical abstract: Abstract: Activated carbon (AC) materials derived from addition of graphene foam, carbon nanotube and expended graphite mixed with polyvinyl alcohol and polyvinylpyrrolidone were synthesized and tested for supercapacitor application. Although the AC obtained from expended graphite shows the smallest specific surface area (SAA), it exhibits the highest electrical double layer capacitance (EDLC) performance with high rate capability and specific capacitance. This material tested in the symmetric configuration works in a large potential window of 1.6 V. More interestingly, the device made out this material gets better in terms of electrochemical performance when subjected to ageing effect with voltage holding for 100 hours. Some tentative reasons for such discrepancy between the SAA and the EDLC are explained.